Regulation of Polygamy in the Conflict of Norms between State Law and Islamic Law in Indonesia - M. Fahmi Habibi; Wakid Evendi (al-Afkar, Journal For Islamic Studies, 2026)
The clash between state law and Islamic law in regulating polygamy in Indonesia reflects a dual approach to viewing this practice. In the state legal system, the practice of polygamy is restricted by strict administrative requirements, such as the obligation to obtain a court permit and the consent of the first wife as essential conditions. Under Islamic law, polygamy is permitted provided the primary condition of the ability to act fairly is met, without the necessity of following formal state regulatory procedures. This study employs a qualitative approach through a literature review, examining various legal regulations and Islamic literature to identify forms of normative conflict and their implications for the practice of polygamy. The research findings clearly indicate that the practice of polygamy without official permission from the court and without following the applicable regulatory procedures in Indonesia is still widespread and has the potential to cause legal conflicts, as well as infringe upon the rights of women and children. Therefore, efforts are needed to harmonize the law in order to prevent illegal practices and ensure the protection of the rights of all parties in a fair and just manner.